2023
DOI: 10.1038/s41419-023-06196-y
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA nHOTAIRM1 is necessary for differentiation and activity of iPSC-derived spinal motor neurons

Paolo Tollis,
Erika Vitiello,
Francesco Migliaccio
et al.

Abstract: The mammalian nervous system is made up of an extraordinary array of diverse cells that form intricate functional connections. The programs underlying cell lineage specification, identity and function of the neuronal subtypes are managed by regulatory proteins and RNAs, which coordinate the succession of steps in a stereotyped temporal order. In the central nervous system (CNS), motor neurons (MNs) are responsible for controlling essential functions such as movement, breathing, and swallowing by integrating si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 59 publications
3
4
0
Order By: Relevance
“…To do that, we combined smFISH and immunofluorescence, targeting nHOTAIRM1, the SG marker G3BP1 and FUS. As previously reported, we observed that nHOTAIRM1 signal was distributed both in the nucleus and in the cytoplasm (Rea et al, 2020;Tollis et al, 2023) (Dormann et al, 2010;Kino et al, 2011). In FUS P525L MNs, where FUS de-localizes in the cytoplasm and participates in SG (Fig 4A, lower panel) (Bosco et al, 2010;Lenzi et al, 2015), nHOTAIRM1 was again recruited to SG.…”
Section: Circ-hdgfrp3 Interacts With Processing Bodies (P-bodies)supporting
confidence: 84%
See 2 more Smart Citations
“…To do that, we combined smFISH and immunofluorescence, targeting nHOTAIRM1, the SG marker G3BP1 and FUS. As previously reported, we observed that nHOTAIRM1 signal was distributed both in the nucleus and in the cytoplasm (Rea et al, 2020;Tollis et al, 2023) (Dormann et al, 2010;Kino et al, 2011). In FUS P525L MNs, where FUS de-localizes in the cytoplasm and participates in SG (Fig 4A, lower panel) (Bosco et al, 2010;Lenzi et al, 2015), nHOTAIRM1 was again recruited to SG.…”
Section: Circ-hdgfrp3 Interacts With Processing Bodies (P-bodies)supporting
confidence: 84%
“…Interestingly, the PCC between nHOTAIRM1 and DCP1A increased in FUS P525L conditions regardless of stress induction (Supplementary Fig 4B). As it was previously demonstrated that nHOTAIRM1 biochemically interacts with FUS (Rea et al, 2020;Tollis et al, 2023) and that mutant FUS binds and sequesters proteins involved in p-bodies formation (Takanashi and Yamaguchi, 2014), these data suggest that the presence of mutant FUS in the cytoplasm could drive the interaction between nHOTAIRM1 and p-bodies.…”
Section: Circ-hdgfrp3 Interacts With Processing Bodies (P-bodies)supporting
confidence: 64%
See 1 more Smart Citation
“…In recent years, functional genomics and transcriptome sequencing technologies have advanced rapidly, revealing an increasing number of factors involved in the regulation of adipogenic differentiation. Among these, long-chain noncoding RNAs (lncRNAs) have received increasing attention due to their important regulatory roles. , LncRNAs are the most abundant type of noncoding RNA and comprise >200 nt long transcripts that play important roles in cell differentiation, growth, development, and onset of many diseases. , LncRNAs exhibit multiple regulatory functions and participate in several important biological processes. They play important regulatory roles in the differentiation of MSCs into adipocytes; however, few studies have explored the role of lncRNAs in adipogenic differentiation .…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 LncRNAs are the most abundant type of noncoding RNA and comprise >200 nt long transcripts that play important roles in cell differentiation, growth, development, and onset of many diseases. 14 , 15 LncRNAs exhibit multiple regulatory functions and participate in several important biological processes. They play important regulatory roles in the differentiation of MSCs into adipocytes; however, few studies have explored the role of lncRNAs in adipogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%